The Role of Russia in the Settlement of the Azerbaijan-Artsakh Conflict - Hasan-Jalalyan, Stepan (History and Culture, 2024)
The purpose of the article, based on the sources related to the issue, is to find out the role of Russia in ensuring security in the South Caucasus in the context of the settlement of the Azerbaijani-Artsakh conflict. The article is written by means of a comparison and comparative study of relevant documents and examination analysis. As a result of the joint examination of facts and documents related to the issue, we came to the conclusion that after the third Azerbaijani-Artsakh war, official Moscow radically revised its approach to the settlement of the Azerbaijani-Artsakh conflict, recording a setback in terms of the expectations of one of the parties to the conflict, Artsakh. Russia, as a traditional regional mediator, through whose mediation negotiations took place between Armenia and Azerbaijan on issues related to both the Azerbaijan-Artsakh conflict and the settlement of relations between Armenia and Azerbaijan, failed to offer mutually acceptable solutions to the conflicting parties.